Ekonomi Media: Perlukah? - Hasan, Bakir (FIkom Unisba, 2006)
Rapid development of communication technology has shaped a new cultural landscape. In effect, the nature of mass media industry also changed a lot. To anticipate this new development, communication discipline needs a new study focused on media economy. Media economy is combination of two perspectives in media studies: business-economy perspective and media communication perspectives. The dimension of media in media economy emphasized three areas: production, content, and audiences. The dimension of economy in media economy studies focused on structure, conduct/policy, and performance. Meanwhile, the management of media corporation are consisted of revenue, cost and profit dimensions.